Developing animated video-based learning with powtoon to foster critical thinking in data presentation - Tomi Listiawan; Jane Eka Sari Radiyah (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2024)
Critical thinking is a vital skill for students to interpret data and make informed decisions, especially in data presentation. This study focuses on developing and evaluating animated video-based learning content using Powtoon software to enhance critical thinking skills in data presentation, following the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) instructional design model. In the Analyze phase, a needs assessment was conducted to identify gaps in students' critical thinking skills regarding data interpretation. During the Design and Develop phases, instructional videos were created to target key critical thinking components, including analysis, interpretation, and evaluation. In the Implement phase, the content was introduced to an experimental group, with a control group using traditional instructional methods. A quasi-experimental approach with pre- and post-tests measured critical thinking improvements in both groups. Results demonstrated a significant increase in critical thinking abilities within the experimental group, with mean scores improving from 55.2 to 82.4, compared to the control group’s increase from 54.8 to 65.3. The study concludes that Powtoon-animated videos are an effective tool for fostering critical thinking in data presentation, offering practical implications for multimedia-assisted learning in mathematics education. Recommendations for further research on technology integration in education are discussed.